A Effect of Pregnancy Spacing and Gravida on The Incidence of Miscarriage - Sofia, Norlaila; Prihatanti, Nur Rochmah; Megawati, Megawati (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2023)
Based on a study on the determinants of maternal death conducted by the Research and Development Agency of Indonesian Ministry of Health in 2012, 4.1% of maternal deaths in Indonesia occurred due to miscarriage. The risk factors for miscarriage involve fetal, maternal and external factors. Although maternal factors only contribute 15% to the incidence of miscarriage, they should be considered important to note, especially in efforts to prevent miscarriage. One of the contributors to high rate of miscarriage cases in South Kalimantan is Banjar District. This study aims to analyze the effect of maternal factors of pregnancy spacing and gravida on the incidence of miscarriage. This was an analytical observational study with a case control design. The case group involved all pregnant women with miscarriage as many as 61 respondents and the control group involved 244 respondents (1:4). The current study was conducted in the work area of Astambul Community Health Center, Banjar District, South Kalimantan in 2022. Secondary data were collected and further analyzed using the chi square test. P value of <0.05 was considered statistically significant. The results of the study revealed that pregnancy spacing and gravida had no significant effect on the incidence of miscarriage with p=0.405 and p=0.341, respectively (P>a). It can be concluded that there was no effect of pregnancy spacing and gravida on the incidence of miscarriage. Keywords: Gravida, Miscarriage, Pregnancy Spacing